Thermodynamic and kinetic properties of calcium hydride - Balakrishnan, Sruthy; Humphries, Terry; Paskevicius, Mark; Buckley, Craig (2023)
Calcium hydride has shown great potential as a hydrogen storage material and as a thermochemical energy storage material. To date, its high operating temperature (above 800 °C) has not only hindered its opportunity for technological application but also prevented detailed determination of its thermodynamics of hydrogen sorption. In addition, calcium metal suffers from high volatility, high corrosivity from Ca (and CaH2), slow kinetics of hydrogen sorption, and the solubility of Ca in CaH2. In this work, a literature review of the wide-ranging thermodynamic properties of CaH2 is provided along with a detailed experimental investigation into the thermodynamic properties of molten and solid CaH2. The thermodynamic values of hydrogen release from both molten and solid CaH2 were determined as ΔHdes (molten CaH2) = 216 ± 10 kJ mol−1.H2, ΔSdes (molten CaH2) = 177 ± 9 J K−1 mol−1.H2, which equates to a 1 bar hydrogen equilibrium temperature for molten CaH2 of 947 ± 65 °C. Similarly, in the solid-state: ΔHdes (solid CaH2) = 172 ± 12 kJ mol−1.H2, ΔSdes (solid CaH2) = 144 ± 10 J K−1 mol−1.H2. Moreover, the activation energy of hydrogen release from CaH2 was also calculated using DSC analysis as Ea = 203 ± 12 kJ mol−1. This study provides the first thermodynamics for the Ca–H system in over 60 years, providing more accurate data on this emerging energy storage material.